The Mediating Role of Job Satisfaction in the Relationship Between Customer Experience and Customer Retention - Iman Maulana; Erni Yuningsih; Yulianingsih Yulianingsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the mediating role of job satisfaction in the relationship between customer experience and customer retention. This research method uses a quantitative approach with primary data obtained through a questionnaire with a Likert scale. The sample size used in this study was 100 Buana Trip customers. Data analysis was conducted using the method Partial Least Squares – Structural Equation Modeling (SEM-PLS). The research results show that Customer Experience has a positive and significant effect on Customer Satisfaction, while Customer Satisfaction has a positive and significant effect on Customer Retention. Furthermore, Customer Experience also has a direct and indirect effect on Customer Retention through Customer Satisfaction.